ANRIL upregulates TGFBR1 to promote idiopathic pulmonary fibrosis in TGF-β1-treated lung fibroblasts via sequestering let-7d-5p - Weidong Wu; Nanding Yu; Weiming Chen; Yong Zhu (Epigenetics)
Idiopathic pulmonary fibrosis (IPF) is a progressive and life-threatening respiratory disease characterized by worsening lung function due to excessive scarring. The objective of this study was to investigate the role of the long non-coding RNA ANRIL (antisense non-coding RNA in the INK4 locus) in the development of IPF. Our research revealed a significant increase in ANRIL expression in pulmonary fibrosis, consistent with prior studies indicating elevated ANRIL levels in fibrotic tissues. In vitro experiments demonstrated that elevated ANRIL expression promoted fibroblast activation, as evidenced by the upregulation of fibrosis-related markers. Mechanistically, we found that ANRIL interacts with let-7d-5p, a microRNA involved in gene regulation, acting as a sponge for let-7d-5p. Functional experiments confirmed a potential influence of let-7d-5p on fibroblast activation through direct interaction with ANRIL. Furthermore, our investigation identified TGFBR1 as a potential mediator of ANRIL’s fibrogenic effects. Silence of TGFBR1 mitigated the fibrotic phenotype induced by ANRIL overexpression. Collectively, these results suggest that ANRIL promotes fibroblast activation and fibrosis development, possibly through the let-7d-5p/TGFBR1 axis, indicating that ANRIL could be a potential therapeutic target for pulmonary fibrosis.